Does Batak Toba Widower Get the Wife’s Family’s Inheritance? - Elfrida Ratnawati Gultom; Endang Pandamdari (Universitas Syiah Kuala, 2021)
The problem that will be discussed in this article is about the inheritance rights of a widower according to the customary inheritance of the Batak Toba, whether the widower according to the customary inheritance law of the Batak Toba gets an inheritance from his wife's family. The type of normative legal research used in this article is supported by references or secondary data as the basic material for research related to the issues discussed, that is the rights of the inheritance of widowers in Batak Toba. The data sources used are primary data and secondary data. The data from the results of this study will be analyzed with a qualitative approach, then will be described descriptively. The conclusion obtained from this study is that a Toba Batak widower, in the customary inheritance law of the Batak Toba does not inherit from his wife's family because the wife is a family member of the husband (honest marriage), because the wife herself does not also get an inheritance fromhis parents, because in Batak Toba community, only sons (his wife's brother) get a share of the inheritance and become the heirs of the wife's parents.